Strategi Pengurangan Emisi Karbon Melalui Reboisasi di Lingkungan Sekolah untuk Mendukung SDGs dalam Mengatasi Perubahan Iklim : EN - Muhzin Z; Ismail Aqsa; Iswahyudi; Achmad Romadin; Andi Muh Rahmat (V-MACHINE: Vocational and Mechanical Community Service Journal, 2024)
The Teaching Campus Program is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs in the form of teaching assistance to empower students in assisting with the learning process in elementary schools in various villages/cities, one of which is PGRI Middle School on Salemo Island, Liukang Tupabbiring Utara District, Pangkajene Islands Regency. , South Sulawesi Province. The Community Service Program carried out at PGRI Salemo Island Middle School is one of the work programs of the 6th generation teaching campus students. This activity includes planting trees around the school environment, and cleaning up the school environment. This program aims to increase students' awareness about how important it is to preserve nature and how big its impact is on the surrounding environment. In this research, the method used is a qualitative method, so as a result of this research, the researcher made direct observations at the implementation location in coordination with the school, and also the campus student field supervisor taught 6 about Community Service activities at PGRI Middle School on Salemo Island, then carried out the activities. planting tree seeds in the school environment which is carried out by working together between students at the teaching campus and also the school. This program also aims to achieve point 13 of the SDGs (Sustainable Development Goals), namely Handling Climate Change, to take immediate action in fighting climate change.